2008
DOI: 10.1002/art.23904
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of T helper cells with fibroblast‐like synoviocytes: Up‐regulation of matrix metalloproteinases by macrophage migration inhibitory factor from both Th1 and Th2 cells

Abstract: Conclusion. MIF is an important Th1 and Th2 cell-derived proinflammatory cytokine that stimulates MMP expression in FLS from arthritic mice, and therefore inhibition of MIF might be a promising target for novel therapeutic strategies in human RA.Macrophage migration inhibitory factor (MIF) is a structurally unique cytokine that is a critical mediator of several acute and chronic inflammatory diseases. Of note, MIF has been prominently detected in supernatants of T cells and in macrophages (1-5). Although it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…We have recently demonstrated that Th2 cytokines stimulate myeloid fibroblast activation via JAK3/STAT6 signaling pathway 13 . Although it is well-established that the biological effects of Th2 cytokines are regulated by IL-4Rα signaling 17, 18 , the precise role of IL-4Rα in activating myeloid fibroblasts and promoting renal fibrosis remains to be determined. In the present study, we have demonstrated that genetic disruption of IL-4Rα inhibits the bone marrow–derived fibroblast accumulation and myofibroblast formation in the kidney and reduces the development of renal fibrosis.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that Th2 cytokines stimulate myeloid fibroblast activation via JAK3/STAT6 signaling pathway 13 . Although it is well-established that the biological effects of Th2 cytokines are regulated by IL-4Rα signaling 17, 18 , the precise role of IL-4Rα in activating myeloid fibroblasts and promoting renal fibrosis remains to be determined. In the present study, we have demonstrated that genetic disruption of IL-4Rα inhibits the bone marrow–derived fibroblast accumulation and myofibroblast formation in the kidney and reduces the development of renal fibrosis.…”
Section: Disscussionmentioning
confidence: 99%
“…Th1 cells produce anti-fibrotic cytokines such as interferon γ (IFN-γ) that suppress myeloid fibroblasts differentiation, while Th2 cells produce the profibrotic cytokines such as IL-4 and IL-13 that promote myeloid fibroblasts differentiation 1719 . IL-4 receptor α (IL-4Rα) is a key component of Th2 cytokine receptor, which mediates Th2 cytokines/signal transducer and activator of transcription 6 (STAT6) signaling pathway transduction and subsequent effector functions 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by synovial membrane hyperplasia and progressive destruction of arthritic joints, as well as inflammatory cell infiltration, including activated CD4 + T cells [2]. The CD4 + T cells play a crucial role in the pathogenesis of RA through their ability to stimulate the secretion of proinflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-1, inducing immunoglobulin production and matrix metalloproteinase secretion leading to osteoclastogenesis [3].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Th2 cells, predominantly producing IL-4 and IL-10, are rarely found in arthritic joints. Anyway, both Th1 and Th2 cells can stimulate MMP expression in arthritic synovial fibroblasts by secretion of macrophage migration inhibitory factor [25]. Tumor necrosis factor alpha (TNFα) is considered as the main proinflammatory cytokine in the pathogenesis of RA [26].…”
Section: Introductionmentioning
confidence: 99%